Stromal MED12 exon 2 mutations in complex fibroadenomas of the breast. Issue 2 (29th December 2020) - da Silva, Edaise M; Beca, Francisco; Sebastiao, Ana Paula Martins; Murray, Melissa P; Silveira, Catarina; Da Cruz Paula, Arnaud; Pareja, Fresia; Wen, Hannah Y; D'Alfonso, Timothy M; Edelweiss, Marcia; Weigelt, Britta; Brogi, Edi; et al.
Abstract : Aims: Here we explore the presence of mediator complex subunit 12 ( MED12 ) exon 2 and telomerase reverse transcriptase ( TERT ) promoter hotspot mutations in complex fibroadenomas (CFAs) of the breast. Methods: The stromal components from 18 CFAs were subjected to Sanger sequencing of MED12 exon 2 and the TERT promoter hotspot loci. The epithelial and stromal components of two MED12 mutated CFAs were subjected to laser capture microdissection, and Sanger sequencing of MED12 exon 2, TERT promoter and PIK3CA exons 9 and 20, separately. Results: MED12 exon 2 mutations were identified in the stroma of 17% of CFAs. The analyses of epithelial and stromal components, microdissected separately, revealed that MED12 mutations were restricted to the stroma. No TERT promoter or PIK3CA mutations in exons 9 and 20 were detected in analysed CFAs. Conclusions: Like conventional fibroadenomas, MED12 exon 2 mutations appear to be restricted to the stromal component of CFAs, supporting the notion that CFAs are stromal neoplasms.